(untitled) - Bloom, Norman D. (Philadelphia, PN., 2000)
This new state-of-the-art atlas covers all of the cancer procedures practiced today with numerous illustrations by Hugh Thomas, a master illustrator. Each chapter begins with anatomical drawings that are synchronized with operative procedures that are descibed in that chapter. The chapter concludes with a case that demonstrates uncommon approaches to surgery written by an authority in that field. The text features discussions on laparoscopic techniques, including video-assisted or minimally invasive techniques applicable to surgical oncology.
Keywords: Cancer; Surgery,Atlases